Ramona and her father eaudiobook - Cleary, Beverly (Ramona Quimby, 2010)
Beverly Cleary's Newbery Honor Book depicts an average middle-class family dealing with the realities of life. With the perfect mix of humor and warmth, Ramona Quimby shines as a spirited girl with her heart set on helping. Seven-year-old Ramona world is turned upside-down when her father unexpectedly loses his job. Things grow tense in the Quimby house, but Ramona resolves to help in any way she can—even downsizing her Christmas list. But with bills piling up and her parents constantly stressed, Ramona wonders if life will ever go back to normal. This beloved Ramona book is as relatable and resonant today as it was when it was written. Boys and girls ages 6-12 will relate to Ramona's funny but real struggles.